Parental Perceptions and Challenges in Supporting the Competency-Based Curriculum (CBC) in Deep Sea Informal Settlement, Loresho, Nairobi County - Mulinya, Sheila; Kimotho, Susan (African Journal of Education and Practice, 2025)
Purpose: The study examined parental perceptions and challenges in supporting the Competency-Based Curriculum (CBC) in the Deep Sea Informal settlement, Loresho, Nairobi County, Kenya. Methodology: The study adopted a descriptive research design, combining qualitative and quantitative approaches to examine parental perceptions and challenges in supporting the Competency-Based Curriculum (CBC) in Deep Sea Slums, Loresho. The target population comprised of parents with children enrolled in CBC schools and a sample of 83 participants was determined using Krejcie and Morgan’s (1970) formula. The selection criteria considered factors such as the number of school-going children per household and parental engagement in CBC-related activities. Stratified random sampling was used to select parents with children enrolled in CBC schools within the Deep Sea informal settlement, ensuring representation across different socio-economic backgrounds. Purposive sampling was applied to select participants for semi-structured interviews and focus group discussions, focusing on parents with varying levels of CBC involvement, age and gender in order to capture diverse perspectives. Data was collected through structured questionnaires and semi-structured interviews. Primary data was then analyzed using descriptive and inferential statistical methods, including correlation, regression as well as ANOVA. The analyzed data was presented in pie charts and tables and interpreted statistically. The study was guided by Joyce Epstein’s Theory of Overlapping Spheres of Influence and Bronfenbrenner’s Ecological Systems Theory to contextualize the overall findings. Findings: The study reveals that 67% of parents lack a comprehensive understanding of CBC, limiting their ability to support their children’s education. This aligns with Epstein’s Theory of Overlapping Spheres of Influence, which highlights the importance of parental engagement in academic success (Epstein, 2011). A lack of comprehension weakens collaboration between schools, families and communities, further exacerbating disparities in education. Boonk et al. (2018) found that parental involvement is positively linked to improved student motivation and performance, reinforcing the necessity of informed parental participation. Additionally, Begi (2020) emphasizes that understanding curriculum requirements is essential for effective home-based learning support. Kariuki & Wanyama (2022) and Mwangi & Kimosop (2021) highlight that low literacy levels in marginalized communities create barriers to the implementation of CBC, while Mwangi & Wambugu (2021) stress that limited parental knowledge on the expectations of CBC reduces engagement in school activities. Bronfenbrenner’s Ecological Systems Theory (1979) provides further insight into these findings by illustrating how multiple environmental systems influence a child’s development. The microsystem, which includes immediate interactions between the child, family and school, is directly affected by parental understanding of CBC, as informed parents can provide better educational support. The mesosystem, which refers to the interactions between these entities through parent-teacher collaboration is weakened when parents lack knowledge about CBC, reducing the effectiveness of learning both at home and in school. The exosystem, encompassing broader societal structures such as education policies and community resources, plays a role in addressing these gaps through parent education programs and community engagement initiatives. Furthermore, Chege & Sifuna (2016) argue that uninformed parents struggle to guide their children academically, widening socio-economic learning disparities. Odundo & Gunga (2018) and Wambua & Otieno (2021) assert that effective implementation of CBC requires informed parental collaboration, while Kabiru & Njenga (2022) emphasize the burden placed on teachers due to inadequate parental support. These findings underscore the need for structured parent education programs to bridge knowledge gaps and enhance parental participation in CBC. Unique Contribution to Theory, Practice and Policy: This study contributes uniquely to theory by expanding the application of Epstein’s Theory of Overlapping Spheres of Influence and Bronfenbrenner’s Ecological Systems Theory in the context of informal settlements, emphasizing how socio-economic barriers influence parental involvement in education. By integrating these theories with the implementation of CBC, the study provides a refined framework for understanding the relationship between parental engagement and learner success in resource-constrained environments. In practice, the study highlights key challenges and proposes actionable solutions that can improve parental support for CBC. It recommends targeted parental training programs, affordable learning resources and enhanced school-parent communication strategies to ensure effective curriculum implementation. Educators, policymakers and community organizations can use these insights to develop localized interventions that empower parents and enhance learning outcomes. From a policy perspective, the findings inform the need for structural reforms to support the implementation of CBC in low-income areas. The study advocates for policy measures such as government-subsidized learning materials, structured parental education programs as well as improved school-community collaboration to bridge the gap in educational equity. By addressing systemic barriers, policymakers can nurture an inclusive and supportive learning environment for all learners.